Effect of Dy3+ Ions on Structural, Thermal and Spectroscopic Properties of L-Threonine Crystals: A Visible Light-Emitting Material - João G. de Oliveira Neto; Otávio C. da Silva Neto; Jéssica A. O. Rodrigues; Jailton R. Viana; Alysson Steimacher; Franciana Pedrochi; Francisco F. de Sousa; Adenilson O. dos Santos (Quantum Beam Science)
In this study, L-threonine crystals (L-thr) containing Dy3+ ions (L-thrDy5 and L-thrDy10) with varying mass concentrations (5% and 10%) were successfully synthesized using a solvent slow evaporation method. The structural properties were characterized by Powder X-ray diffraction and Rietveld refinement. The data revealed that all three samples crystallized in orthorhombic symmetry (P212121-space group) and presented four molecules per unit cell (Z = 4). However, the addition of Dy3+ ions induced a dilation effect in the lattice parameters and cell volume of the organic structure. Additionally, the average crystallite size, lattice microstrain, percentage of void centers, and Hirshfeld surface were calculated for the crystals. Thermogravimetric and differential thermal analysis experiments showed that L-thr containing Dy3+ ions are thermally stable up to 214 °C. Fourier transform infrared and Raman spectroscopy results indicated that the Dy3+ ions interact indirectly with the L-thr molecule via hydrogen bonds, slightly affecting the crystalline structure of the amino acid. Optical analysis in the ultraviolet–visible region displayed eight absorption bands associated with the electronic transitions characteristic of Dy3+ ions in samples containing lanthanides. Furthermore, L-thrDy5 and L-thrDy10 crystals, when optically excited at 385 nm, exhibited three photoluminescence bands centered around approximately 554, 575, and 652 nm, corresponding to the 4F7/2 → 6H11/2, 4F9/2 → 6H13/2, and 4F9/2 → 6H11/2 de-excitations. Therefore, this study demonstrated that L-thr crystals containing Dy3+ ions are promising candidates for the development of optical materials due to their favorable physical and chemical properties. Additionally, it is noteworthy that the synthesis of these systems is cost-effective, and the synthesis method used is efficient.